Psychological Responses to Home-Working Practices: A Network Analysis of Relationships with Health Behaviour and Wellbeing - Samuel Keightley; Ayla Pollmann; Benjamin Gardner; Myanna Duncan (Behavioral Sciences)
Working at home, rather than in the workplace, has been suggested to affect office-based workers’ health and wellbeing. This exploratory, cross-sectional study sought to identify discrete psychological responses to home-working practices and investigate their relationship with engagement in health-related behaviours and wellbeing. A sample of 491 home-workers completed a survey assessing ten psychological responses to home-working (e.g., the ability to ‘switch off’ from work), ten health behaviour indices (e.g., sleep trouble), and seven wellbeing indices. Network Analysis modelled relationships between these variables. Results showed four clusters of psychological responses to home-working practices (representing ‘home-working independence’, ‘home-work transition’, ‘daily work pressure’, and ‘work-day forecasting’). Variables within these clusters linked to health behaviour and wellbeing: perceptions of workload manageability, ability to switch off from work, homeworking autonomy, and planning and organising a home-working day had cascading influences on indicators of health, health behaviours, and wellbeing. The findings point to a complex system of potential health and wellbeing consequences of working from home. Further evidence is needed to establish truly causal relationships; nonetheless, our findings call for the development of public health initiatives and organisational policies to support the adoption of home-working practices to benefit the health and wellbeing of home-workers.